Embedded Junior High School English Reading Classes with Teaching-Learning-Assessment Integration - Li, Xinyao; Liu, Yunfei (Journal of Educational Research and Policies, 2025)
Reading instruction, as a vital component of English teaching, is obligated to keep abreast of the times and explore a more efficient and beneficial teaching model. The integration of teaching, learning, and assessment stands as a crucial content in the new-era reform of English curriculum, serving to further guide teachers in optimizing their teaching practices. The application of the teaching,learning-assessment integration model in English reading classes can effectively boost the enhancement of students’ core competencies, encompassing language ability, thinking quality, and learning ability. In practical teaching scenarios, teaching, learning, and assessment should be treated as an organic whole, with assessment permeating every aspect of the entire teaching process. This paper endeavors to explore the integration of teaching-learning-assessment into junior high school reading classes by combining relevant practical cases, aiming to provide valuable insights for educational practitioners.